Immunomodulatory potential of acemannan (polysaccharide from Aloe vera) against radiation induced mortality in Swiss albino mice. Issue 1 (2nd January 2016) - Kumar, Sumit; Tiku, Ashu Bhan
Abstract : Plant polysaccharides have been reported to stimulate growth, differentiation and proliferation of hematopoietic progenitor and stem cells to protect against the deleterious effects of radiations. This study evaluated the radioprotective potential of acemannan, a major polysaccharide component of aloe vera gel. Treatment of mice with 50 mg/kg body weight of acemannan by oral gavage for 7 days was able to protect against the radiation-induced mortality. Seven-day pretreatment or post-treatment of mice with acemannan resulted in the increase in median survival by 60 and 20%, respectively. The decrease in mortality can be attributed to the induction of hematopoiesis (peripheral lymphocytes counts, spleen cellularity, spleen index) and the upregulation of cytokines like TNF- α and IL-1 by acemannan in irradiated mice. Data indicate that acemannan has the ability to protect mice against radiation-induced mortality by immunomodulation and can be developed as a radiation damage mitigation agent.